2015
DOI: 10.5001/omj.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

Khat Use: History and Heart Failure

Abstract: Recent reports suggest that 20 million people worldwide are regularly using khat as a stimulant, even though the habit of chewing khat is known to cause serious health issues. Historical evidence suggests khat use has existed since the 13th century in Ethiopia and the southwestern Arabian regions even before the cultivation and use of coffee. In the past three decades, its availability and use spread all over the world including the United States and Europe. Most of the consumers in the Western world are immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 35 publications
2
88
0
Order By: Relevance
“…This study found a higher miraa use among participants who were born out of Eastleigh, of 53.3% meaning they could have migrated to this area compared to those born in Eastleigh, (43.8%). This is similar to other studies, that indicated that miraa use among immigrants from Eastern Africa and the Middle East to the Western world had higher miraa use, [17]. The same was also pointed by Young et al, 2016 among youth immigrants from Africa in Australia, [20].…”
Section: Prevalence Of Miraa Use Per Socio-demographic Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…This study found a higher miraa use among participants who were born out of Eastleigh, of 53.3% meaning they could have migrated to this area compared to those born in Eastleigh, (43.8%). This is similar to other studies, that indicated that miraa use among immigrants from Eastern Africa and the Middle East to the Western world had higher miraa use, [17]. The same was also pointed by Young et al, 2016 among youth immigrants from Africa in Australia, [20].…”
Section: Prevalence Of Miraa Use Per Socio-demographic Characteristicssupporting
confidence: 91%
“…In addition, miraa use has been seen to increase physical health problems that include gastrointestinal disorders, high blood pressure, heart failure, autoimmune hepatitis, poor health among those living with HIV/AIDS, poor physical health problems, low birth weight among pregnant women, H. pylori infection, and under nutrition,. " [15][16][17][18][19][20][21][22]". All the above lead to increased financial problems, poor academic functioning and poorer quality of life, [23].…”
Section: Effects Of Miraamentioning
confidence: 99%
“…Cathinone in particular has central nervous system stimulation properties that are similar to amphetamine, producing euphoria and increased alertness in its users. Khat use is an established risk factor for systemic hypertension (140), acute myocardial infarction (AMI) (141) and dilated cardiomyopathy (142). The mechanism by which khat use contributes to AMI appears to be coronary vasospasm and not coronary artery disease (CAD).…”
Section: Khatmentioning
confidence: 99%
“…Sir Richard Burton described, Khat was introduced to Yemen from Abyssinia in the 15th century (Burton, 1966 cited in Al-Habeshi andSkaug, 2005;Saeed, 1987). El-Menyar et al (2015) reported that the plant is native to Ethiopia and Arabian Peninsula but it is produced widely in Yemen than that of Ethiopia (Saeed, 1987). Gebissa (2008) corroborated that Khat is originated in eastern part of Ethiopia; specifically in Harar.…”
Section: Historical Precedents Of Khat: Overviewmentioning
confidence: 99%